2007
DOI: 10.1021/ie060597c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Transversal Hot Zones in a Shallow Packed Bed Reactor during Oxidation of Mixtures of C3H6 and CO

Abstract: The evolution and motions of transversal hot zones on the top of a shallow packed bed reactor, in which the atmospheric oxidation of either propylene or its mixture with CO took place, were studied using infrared thermography. The hot regions were separated by a sharp temperature front from the adjacent colder region (ΔT ∼ 50 °C). The period of the oscillations of mixtures of propylene and carbon monoxide was about 20 times shorter than those of CO and about 2 times shorter than those of propylene. This indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Marwaha and Luss9 showed that various 2‐dimensional temperature patterns may form on the surface of a thin, hollow cylindrical catalytic reactor used to carry out an oscillatory reaction. Sundarram and Luss24 conducted two reactions in the same shallow packed‐bed reactor. These experiments showed that the dynamics of the hot zones were mainly influenced by the reaction kinetics and not by the transport parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Marwaha and Luss9 showed that various 2‐dimensional temperature patterns may form on the surface of a thin, hollow cylindrical catalytic reactor used to carry out an oscillatory reaction. Sundarram and Luss24 conducted two reactions in the same shallow packed‐bed reactor. These experiments showed that the dynamics of the hot zones were mainly influenced by the reaction kinetics and not by the transport parameters.…”
Section: Introductionmentioning
confidence: 99%
“…It is experimentally difficult to isolate the impact of individual rate processes. Sundarram and Luss observed striking differences in the pattern dynamics during the oxidation of a single reactant (either CO or propylene) and of a mixture (CO and propylene) in the same reactor. For example, using the reactants mixture the frequency of the oscillations was 20 times higher than when using only CO and twice higher than when the feed contained only propylene.…”
Section: Experimental Observations Of Hot Zones In Packed Bed Reactorsmentioning
confidence: 99%
“…(III) Range of vessel temperature over which nonuniform states existed at different flow rates for single reactant feed (CO or C 3 H 6 ) and for mixture (CO + C 3 H 6 ). Adapted with permission from ref . Copyright 2007 American Chemical Society.…”
Section: Experimental Observations Of Hot Zones In Packed Bed Reactorsmentioning
confidence: 99%
“…18 While breathing, antiphase and rotating patterns with large periods have been reported to form in shallow reactors during CO oxidation, 19,20 similar nonuniform states were observed during oxidation of propylene with periods of oscillation 10 times shorter. 16 Lack of a suitable noninvasive, in situ technique for accurate local temperature measurement 21 in a large commercial reactor limits the ability to detect formation of hot zones deep inside a PBR and to understand their characteristics. However, mathematical modeling provides an alternative approach to systematically predict and analyze hot zone formation and dynamics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using infrared imaging configured appropriately on various model lab- and bench-scale packed-bed reactors such as a radial flow reactor, thin cylindrical shell reactor, shallow PBRs, or catalytic glass fiber cloth, spatiotemporal patterns on top of or curved surface of the reactor have been detected experimentally for exothermic reactions such as CO oxidation, ,, simultaneous ethylene and acetylene hydrogenation, oxidation of a mixture of propylene and CO, and oxidative coupling of methane . For a detailed review of these, see Luss and Sheintuch .…”
Section: Introductionmentioning
confidence: 99%